Manajemen Krisis PT Antam dalam Memperbaiki Citra Pasca Kasus Korupsi 109 Ton Emas - Diaz, Carolina Fernanda; Azmi, Fina Malika; Salsabila, Rara; Meitana, Nabila Putri; Zebua, Winda Dwi Astuti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
PT. Antam is a mining company under the auspices of BUMN which manages various mineral resources such as nickel ore, ferronickel, gold, silver, bauxite and also coal. In May 2024 it was circulated that six high-ranking officials of PT. Antam committed corruption and produced 109 tonnes of illegal gold and forged stamps. The aim of this research is how the crisis management strategy of PT. Antam and how does PT. Antam improved its image and reputation after this news. The theory used in this research is William Benoit regarding how organizations respond to threats to their image after experiencing a crisis, namely image repair. The methodusedin this researchis qualitativeby collecting data from literature studies, data collection, and monitoring news in online media. The results of this research show that from the image repair theory with crisis management at PT. Antam received an award as a company with a good reputation and performance, reducing the amount of news about this case.